Analisis Kredit Bermasalah Sebagai Antisipasi Terhadap Krisis Perbankan di Indonesia (Kasus pada Kredit Properti BTN) - Ambarwati, Erni; Syafitri, Wildan (Jurnal Ilmiah Mahasiswa FEB, 2014)
Bank  as  an  intermediary  financial  institutions will  be  able  to  be  the  cause  of  the  crisis resulting from increased non performing loans in the form of arrears interest payments, principal loan  or  both.  This  research  focuses  to  assess  the  potential  due  to  credit  crisis  in  the  country troubled  by  knowing  variable  influence monetary  is  inflation,  interest  rate  on mortgage  loans, exchange rate and bank performance is LDR, CAR and BOPO against non performing loans of the Bank Tabungan Negara  in  the  short  term and  long  term. Loans at a bank can be  seen  from  the comparison  loans  and  the  amount  of  the  credits  distributed  known  as  the  ratio  of  the  Non Performing Loan  ( NPL). The analysis of  the data used  in  this  study  is Erorr Correction Model (ECM)/ model correction of a  fault. Using  this method be analyzed  the short-term and  long-term between  the  independent variable of  the dependent variable and engineering analysis  to correct imbalances long-term (speed of adjusment). The results of  this study shows  that  in  the short  term positive effect of  inflation variables, interest rates on mortgage loans have positive effect, exchange rate not have negative effects, LDR have  positive  effect, CAR not  have  positive  effect  and  BOPO  have positive  effect  on  the  non-performing loans at Bank Tabungan Negara. While in the long run variable inflation it has some positive  effects,  interest  rates on mortgage  loans have a negative  effect,  exchange  rate not have negative  effects,  LDR  have  positive  effects, CAR  have  positive  effects  and  BOPO  have  positive effects  on  the  non  performing  loans  at  Bank  Tabungan  Negara.  Increase  in  numbers  non performing  loans at Bank Tabungan Negara during a period of  research make bank potentially facing  the  crisis  if  trust banking  customers,  investors and markets decline  so withdrawing  their customers in large numbers or bank rush that can disturb liquidity at Bank Tabungan Negara. Key Words: Non Performing Loans, Inflation, Interest Rate on Mortage Loan, Exchange Rate, LDR, CAR, BOPO, Banking Crisis, ECM Model